KETIDAKADILAN GENDER DALAM NOVEL DRUPADI KARYA SENO GUMIRA AJIDARMA (GENDER INJUSTICE IN THE NOVEL DRUPADI BY SENO GUMIRA AJIDARMA - Tati Akhbaryah (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
AbstractGender Injustice in The Novel Drupadi by Seno Gumira Ajidarma. This study aims todescribe gender injustice in the Novel "Drupadi" and its effects on Drupadi characters.The Novel "Drupadi" is a research data source because it raises basic humanitarianissues, namely women, violence, gender injustice. The context is relevant to everyday lifeand is still a problem in life. In this study, the writer discusses the following issues: First,forms of gender injustice in the Novel "Drupadi." Second, the influence of genderinjustice on Drupadi's character. Third, action against Drupadi figures shows genderinjustice.This study uses a feminist literary criticism approach because it focuses onfemale characters / unequal gender relations. The method used is a qualitativedescription; this method is to understand the forms of gender injustice contained in theDrupadi novel. The results showed: First, the existence of forms of gender injustice,namely (1)) Stereotypes: (2) Subordination (3) Marginalization (4) Violence: physical,psychological, verbal, and sexual abuse (5) Multiple burdens Second, the gender injusticeexperienced by Drupadi had a big impact on his personality. Two characteristicspossessed by Drupadi, namely good and bad qualities, form the image of feminist womenin Drupadi. The gender injustice experienced by the Drupadi figure pushed her to defendher rights and honor from the pressure of male power so that she could determine herown path in life. Third, Drupadi's resistance action through Expressing opinions,contesting, fighting. Drupadi's resistance was manifested in acts of rejection, disguises,pledges, and acts of revenge.Keywords: gender injustice, stereotypes, subordination, marginalization, violence, thedouble burdenAbstrakKetidakadilan Gender dalam Novel Drupadi karya Seno Gumira Ajidarma. Penelitianini bertujuan untuk mendeskripsikan ketidakadilan gender dalam novel Drupadi danpengaruhnya pada diri tokoh Drupadi. Novel Drupadi menjadi sumber data penelitiankarena mengangkat masalah kemanusiaan yang mendasar, yaitu tentang perempuan,kekerasan, ketidakadilan gender. Adapun konteksnya relevan dengan kehidupan seharihari dan sampai saat ini masih menjadi masalah dalam kehidupan. Pada penelitian inipenulis membahas tentang masalah: Pertama, bentuk-bentuk ketidakadilan gender dalamnovel Drupadi karya Seno Gumira Ajidarma. Kedua, pengaruh ketidakadilan genderterhadap diri tokoh Drupadi. Ketiga, aksi perlawanan tokoh Drupadi terhadapketidakadilan gender. Penelitian ini menggunakan pendekatan kritik sastra feminis karenafokus perhatiannya pada tokoh perempuan/relasi gender yang timpang. Metode yangdigunakan adalah deskripsi kualitatif, metode ini untuk memahami bentuk-bentukketidakadilan gender yang terdapat dalam novel Drupadi. Hasil penelitian menunjukkan:Pertama, adanya bentuk-bentuk ketidakadilan gender, yaitu (1) Stereotif (2) Subordinasi(3) Marginalisasi (4) Kekerasan: Fisik, psikis, verbal dan seksual.(5) Beban ganda.Kedua, ketidakadilan gender yang dialami Drupadi berpengaruh besar padakepribadiannya. Dua sifat yang dimiliki Drupadi, yakni sifat baik dan sifat burukmembentuk citra perempuan feminis dalam diri Drupadi. Ketidakadilan gender yangdialami tokoh Drupadi mendorong dirinya untuk membela hak dan kehormatan daritekanan kekuasaan laki-laki agar ia bisa menentukan jalan hidupnya sendiri. Ketiga, aksiperlawanan Drupadi melalui: Penyampaian pendapat, menggugat, melawan. PerlawananDrupadi diwujudkan dalam aksi penolakan, penyamaran, sumpah janji dan aksi balasdendam.Kata-kata kunci: ketidakadilan gender, stereotif, subordinasi, marginalisasi, kekerasan,beban ganda